Implicature Of Directive Utterances Used In The Magic Of Belle Isle Movie - Indahsari, Fitri Fajar Nur, Agus Wijayanto,Ph.D, Dra. Siti Zuhriah Ariatmi, M.Hum (2015)
This study belongs to descriptive qualitative research. The purpose of the study are to describes the linguistic forms of directive utterances, the implicature of directive utterances and the maxim violation of directive utterances used in The Magic of Belle Isle movie. The data are taken from the movie manuscript of The Magic of Belle Isle. The writer uses documentation and observation in collecting the data. The results of the research show that: 1) There are two word forms of directive utterance namely: verb and determiner or 3,39% from the numbers of data; and five sentence form of directive utterance there are, 31 numbers of data or 52,54% of declarative sentence, 14 numbers of data or 23,73% of imperative sentence, 7 numbers of data or 11,86% of interrogative sentence, 4 numbers of data or 6,78% of conditional sentence, and 1 number of data or 1,70% mixed interrogative-conditional sentence. 2) From 59 numbers of data, 23 numbers of data or 39% belong to conventional implicature and 36 numbers of data or 61% belong to conversational implicature. 3) From 36 numbers of data of conversational implicature, the writer finds four types of violation maxim of directive utterance used in The Magic of Belle Isle movie: 11 numbers of data or 30,56% violated the maxim of quality, 9 numbers of data or 25% violated the maxim of quantity, 7 numbers of data or 19,44% violated the maxim of manner, and 9 numbers of data or 25% violated the maxim of relevance. The research also finds the relation of implicature, linguistics form and the violation maxim. In the term of conventional implicature all kinds of linguistics forms can be used to produce directive utterance since the linguistics forms uses do not require special context in interpreting the meaning or the illocutionary act of the utterance. In conversational implicature, interrogative sentence and declarative sentence mostly break the maxim of quantity. The use of declarative sentence could be the most effective to produce the violation maxim of quantity, to add some utterance or to give less information as the function of declarative sentence is to declare or to inform. In interrogative sentence, the speaker violated the maxim of quantity of giving less information to the addressee since the function of interrogative sentence is to ask somebody without giving the evidence. Imperative sentence mostly break the maxim of quality which is could be the function of the imperative sentence is to commanding the addressee. The addressee mostly give command by the lack of the evidence or might be said what is false. Conditional sentence is used have the same frequent in violating the maxim of quantity, manner, and relevance. By using the conditional sentence, the speaker could be able to explore their utterances even to give more information, less information, makes an ambiguous, and irrelevance utterance.